2020
DOI: 10.3389/fmicb.2020.548737
|View full text |Cite
|
Sign up to set email alerts
|

Cryptosporidium parvum Infection Depletes Butyrate Producer Bacteria in Goat Kid Microbiome

Abstract: Cryptosporidium parvum is an important apicomplexan parasite infecting ruminants and humans. We characterized the impact of C. parvum infection on the goat kid microbiome. C. parvum was orally administered to parasite-naïve goats, and infection was monitored for 26 days in fecal samples using immunofluorescence assay and qPCR tests. Age-matched goats served as uninfected controls. A reduction in body weight gain, diarrhea, and dehydration were observed in infected goats compared to the uninfected controls. Inf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 60 publications
1
19
0
Order By: Relevance
“…However, it should be noted that in the current study, the mice did not show clinical signs of cryptosporidiosis, making them possibly asymptomatic carriers of the parasite. However, in other studies involving goats, which showed mild to severe clinical symptoms of cryptosporidiosis (diarrhoea, hypothermia, growth retardation, and mortality), bacterial species associated with SCFA production have been shown to be depleted, thereby impacting overall SCFA biosynthesis pathways [31].…”
Section: Cryptosporidiosis Dynamics In the Gutmentioning
confidence: 96%
“…However, it should be noted that in the current study, the mice did not show clinical signs of cryptosporidiosis, making them possibly asymptomatic carriers of the parasite. However, in other studies involving goats, which showed mild to severe clinical symptoms of cryptosporidiosis (diarrhoea, hypothermia, growth retardation, and mortality), bacterial species associated with SCFA production have been shown to be depleted, thereby impacting overall SCFA biosynthesis pathways [31].…”
Section: Cryptosporidiosis Dynamics In the Gutmentioning
confidence: 96%
“…Studies comparing some of the methods (i.e., PICRUSt, PICRUSt2, and Tax4Fun) revealed that no method was superior to another [ 76 ], and PICRUSt2 has been applied on samples from various animals, including arthropods (e.g., Ixodes spp. [ 77 ], nematodes (e.g., Caenorhabditis elegans , [ 78 ]), birds (e.g., Serinus canaria domestica [ 79 ]), and mammals (e.g., humans [ 39 ], goats [ 80 ], and bats [ 21 ], among others. In our study, analysis of the functional prediction for multiple bat species, which are taxonomically different and have distinct feeding strategies, showed that frugivorous bats are very different from insectivorous, carnivores, or blood-feeders.…”
Section: Discussionmentioning
confidence: 99%
“…C. parvum was orally administered to parasite-naïve goats, and infection was monitored for 26 days in fecal samples. C. parvum decreased the abundance of butyrate-producing pathways in bacteria and increased mucosal inflammation and tissue repair [ 110 ].…”
Section: Microbiota and Cryptosporidium Sppmentioning
confidence: 99%